Signal Assisted Clipping Distortion Recovery for OFDM Systems Based on Compressed Sensing - Ning Li; Mingjin Li; Zhongliang Deng (IEEE Access, 2020)
The clipping distortion, which generated in the orthogonal frequency division multiplexing systems will have a serious impact on the bit error performance, can be mitigated by clipping distortion recovery techniques. In this paper, we propose a compressed sensing (CS) based signal assisted Clipping Distortion Recovery (saCDR). At the transmitter, we use the clipping position to generate an auxiliary signal to transmit sparse information. The proposed method solves the problem that it is difficult to obtain the sparsity K when the receiver uses orthogonal matching pursuit (OMP) for clipping distortion recovery. At the receiver, we propose the location-assisted OMP algorithm (laOMP), which greatly reduces the system complexity and can still ensure good recovery performance under severe clipping scenarios. Simulation results show that the proposed method can obtain good bit error rate performance under different channels.